InSight Constraints on the Global Character of the Martian Crust. Issue 5 (18th May 2022) - Wieczorek, Mark A.; Broquet, Adrien; McLennan, Scott M.; Rivoldini, Attilio; Golombek, Matthew; Antonangeli, Daniele; Beghein, Caroline; Giardini, Domenico; Gudkova, Tamara; Gyalay, Szilárd; Johnson, Catherine L.; Joshi, Rakshit; et al.
Abstract: Analyses of seismic data from the InSight mission have provided the first in situ constraints on the thickness of the crust of Mars. These crustal thickness constraints are currently limited to beneath the lander that is located in the northern lowlands, and we use gravity and topography data to construct global crustal thickness models that satisfy the seismic data. These models consider a range of possible mantle and core density profiles, a range of crustal densities, a low‐density surface layer, and the possibility that the crustal density of the northern lowlands is greater than that of the southern highlands. Using the preferred InSight three‐layer seismic model of the crust, the average crustal thickness of the planet is found to lie between 30 and 72 km. Depending on the choice of the upper mantle density, the maximum permissible density of the northern lowlands and southern highlands crust is constrained to be between 2, 850 and 3, 100 kg m −3 . These crustal densities are lower than typical Martian basaltic materials and are consistent with a crust that is on average more felsic than the materials found at the surface. We argue that a substantial portion of the crust of Mars is a primary crust that formed during the initial differentiation of the planet. Various hypotheses for the origin of the observed intracrustal seisimic layers are assessed, with our preferred interpretation including thick volcanic deposits, ejecta from the Utopia basin, porosity closure, and differentiation products of a Borealis impact melt sheet. Plain Language Summary: The crust, mantle and core are the three major geochemical layers that make up a planet. Before NASA's InSight mission, the thickness of the crust of Mars was inferred using indirect techniques, including analyses of gravity data collected from orbit and the composition of surface rocks. Estimates for the average thickness using these techniques spanned the range from 27 to 118 km. Analyses of data collected by the InSight seismometer have provided us with the first direct seismic measurement of the thickness of the crust, but this measurement is only for beneath the lander that is located in the northern lowlands where the crust is expected to be thinner than average. In this work, gravity and topography data are used to construct global crustal thickness models that satisfy the new seismic constraints. The average crustal thickness is found to be somewhere between 32 and 70 km, and the average density of the crust can be no larger than 3, 100 kg m −3 . This bulk crustal density is lower than most typical Martian basaltic materials, suggesting that the bulk composition of the crust is different from the volcanic materials at its surface. Key Points: Gravity, topography, and InSight seismic constraints are used to determine the average thickness of the crust of Mars The average thickness of the crust is between 30 and 72 km, and the maximum permissible crustal density is between 2, 850 and 3, 100 kg m −3 The inferred crustal densities are compatible with a crust that is more felsic than typical Martian basaltic materials